Dynamics of neutrophil phenotype and function in sickle cell disease - Aafke E. Gaartman; Aafke E. Gaartman; Lydian A. de Ligt; Lydian A. de Ligt; Lydian A. de Ligt; Boukje M. Beuger; Anton T. J. Tool; Martijn Veldthuis; Taco W. Kuijpers; Taco W. Kuijpers; Rob van Zwieten; Bart J. Biemond; et al. (Frontiers in Immunology)
IntroductionWhile sickle cell disease (SCD) is primarily acknowledged as an erythrocyte disorder, emerging evidence suggests a role for altered neutrophil phenotype and function in SCD pathophysiology and disease severity. Given the conflicting findings in previous studies, we performed a comprehensive exploration of neutrophil characteristics in SCD patients during steady state and vaso-occlusive crisis (VOC), as well as in response to therapeutic interventions.MethodsNeutrophil phenotype was assessed by flow cytometry and functional properties were evaluated by measurement of neutrophil adhesion and reactive oxygen species (ROS) production.ResultsA total of 49 SCD patients (of whom 19 during both steady state and VOC) along with 16 healthy ethnicity-matched and 30 non-matched controls, were included in the study. Differences were observed between neutrophils from patients compared to controls and between control groups. Neutrophil phenotype was more activated in SCD patients compared to non-matched controls. Neutrophil adhesion was increased in steady-state SCD patients compared to both ethnicity-matched and non-matched controls.DiscussionWhile neutrophil phenotype in SCD patients differed from non-matched controls, in contrast to earlier studies, the differences in neutrophil phenotype between SCD patients and ethnicity-matched controls were modest. In vitro neutrophil adhesion was higher in SCD patients than in ethnicity-matched and non-matched controls. Potential explanations for the discrepancies between earlier findings and our study are the large variation in neutrophil phenotypes between individuals, methodological variability between studies and differences in the time interval between blood sample collection and the measurements.